A Simulation Approach for Performance Measures of Food Manufacturing Process - Nerda Zura Zaibidi; Siti Aisyah Binti Yacob; Nur Fitrah Binti Mat Isa (International Journal of Supply Chain Management, 2020)
In Malaysia, Small and Medium-sized Enterprise (SME) of food manufacturing industry is the second highest contributor in manufacturing sector and plays an important role to the economic development and growth. Hence, monitoring process of the industry should be occupied comprehensively and appropriately even though it is categorized under small- scale organization. Shrimp paste production is one of the small-scale food production that is popular in Malaysia. In this study, a performance of shrimp paste production is measured by using simulation approach. A discrete event simulation model is developed to illustrate the processes in the production line which involved four major processes. From the model, it is estimated that the average process time taken to produce 2000 pieces of shrimp paste is 235.13 minutes while the average waiting time taken in the operation system is 89.21 minutes. The findings also show that the bottleneck of the production process is found to be at packaging process and some of the resources are not fully utilized.